Uktena riparia n. gen., n. sp. (Annelida, Clitellata, Lumbriculidae), a new spermatophore-producing oligochaete - Fend, Steven V.; Rodriguez, Pilar; Lenat, David R. (Zootaxa, 2015)
Uktena riparia n. gen., n. sp. has been collected in hyporheic habitats at several sites in North Carolina, southeastern USA. The genus is defined by unusual characters related to reproductive structures, including the formation of encapsulated spermatophores for sperm transfer and large bundles of genital chaetae, both previously unknown in the Lumbriculidae. The simultaneous occurrence of both spermatophores and spermathecae is rare in the microdrile oligochaetes. Uktena spermatophores appear more similar to those reported in leeches than to those in other microdrile oligochaete families. Possible synapomorphies associating Uktena with the genera Kincaidiana and Guestphalinus include a filiform, ringed proboscis, a forward shift of reproductive organs relative to the usual position in the family, and spermathecae in the atrial segment. The new species adds to the already diverse, endemic lumbriculid fauna of the North Carolina Sandhills ecoregion.